The effectiveness of treatment based on acceptance and commitment on Self-Control and appearance schema in obese women without diet - Pooyanmehr, Jafar; Zarehneyestanak, Mohammad; Tabatabaeinejad, Fatemeh Sadat; Khoshakhlagh, Hasan. (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The purpose of this study was to investigate the effectiveness of acceptance and commitment therapy on self-control and appearance schema in obese women without a diet. Methods: It was a semi-experimental research design of pre-test-post-test and follow-up type with an unequal control group. The statistical population of this research included women with a body mass index above 30 who referred to the Noor Nutrition and Obesity Treatment Clinic in the city of Ray in the year 2021. The sample size consisted of 30 people who were selected by available sampling method and were placed in two experimental and control groups. For the experimental group, treatment based on acceptance and commitment was implemented based on the package of Hayes et al. (2006), while the control group did not receive training. The research tools included the self-control scale of Tanjeni et al. (2004) and the appearance schema questionnaire of Kash, Melnik and Harbosky (2004). Data analysis was done using descriptive statistics and analysis of variance test with repeated measurements in spss software version 26. Results: The results showed that the treatment based on acceptance and commitment on self-control (F=24.25, P